2014
DOI: 10.1136/bcr-2013-200282
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone-induced dystonia: a rare and troublesome complication

Abstract: Domperidone is a commonly prescribed antiemetic drug but its side effects are rarely seen. Extrapyramidal side effects are a very rare complication of the drug occurring in 1/10,000 population. They usually occur in infants and very young children due to a poorly developed blood-brain barrier. We report a case of acute dystonia in a 13-year-old boy induced by domperidone. The boy was treated for viral fever and was started on domperidone 30 mg/day, sustained release form (0.7 mg/kg/day), for persistent vomitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…First, our model outputs that A03F (propulsive) had a high importance ratio for inducing anaphylaxis, but this is not listed in the SIDER database. However, we found that Dhakal et al 32 mentioned anaphylaxis as a very rare side effect of Domperidone. Second, our model said G04C (drugs used in benign prostatic hypertrophy) was important for inducing agranulocytosis, but this is also not listed in the SIDER database.…”
Section: Discussionmentioning
confidence: 66%
“…First, our model outputs that A03F (propulsive) had a high importance ratio for inducing anaphylaxis, but this is not listed in the SIDER database. However, we found that Dhakal et al 32 mentioned anaphylaxis as a very rare side effect of Domperidone. Second, our model said G04C (drugs used in benign prostatic hypertrophy) was important for inducing agranulocytosis, but this is also not listed in the SIDER database.…”
Section: Discussionmentioning
confidence: 66%
“…Acute dystonia is a frequent side effect of antidopaminergic drugs. At paediatric age, DID is most commonly caused by antiemetic drugs (eg, metoclopramide and domperidone),3 4 followed by antipsychotic drugs (eg, haloperidol) used for epilepsy or psychiatric diseases 5. Nevertheless, data on the causes, clinical features and management of DID in children are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapyramidal symptoms such as dystonias, Parkinsonism, akathisia, and tardive dyskinesia are side effects of centrally acting D2 antagonists, such as antipsychotics. Rarely, these side effects are observed with domperidone use, especially in infants and young children due to the poorly developed blood-brain barrier [5]. Drug-induced dystonia may be confused with different conditions such as partial seizure, encephalitis, tetany, tetanus, and electrolyte imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…Domperidone-induced acute dystonias are reversible and treated with parenteral administration of anticholinergics such as benztropine or diphenhydramine. Antihistamines having an anticholinergic action such as promethazine are also helpful [5,9].…”
Section: Discussionmentioning
confidence: 99%